THE INFLUENCE OF STORE ATMOSPHERE, SOCIAL MEDIA AND WORD OF MOUTH ON CONSUMER'S BUYING INTEREST IN TANJUNG BALAI KARIMUN'S POTOCOFFEE MILKSHAKE - Nusantara, Aprizal Bahana; Fadli, Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine the effect of store atmosphere, social media and word of mouth on consumers' buying interest in Potocoffee Milkshake Tanjung Balai Karimun. This study uses the method used in this study is descriptive and quantitative statistics with explanatory research models. Data collection was carried out using a questionnaire consisting of 34 statements and the sample consisted of 100 respondents using the accidental sampling method. Research data was collected using a questionnaire that was measured using a Likert scale and processed using SEM PLS 4 to process data and test hypotheses. The results of the study show that the influence of store atmosphere, social media and word of mouth has a significant effect on consumer buying interest. Keywords: Store Atmosphere, Media Social, Word Of Mouth, Consumer Buying Interest